Cohort intelligence : a socio-inspired optimization method - Kulkarni, Anand Jayant; Krishnasamy, Ganesh; Abraham, Ajith, 1968- (Springer, 2017)
This Volume discusses the underlying principles and analysis of the different concepts associated with an emerging socio-inspired optimization tool referred to as Cohort Intelligence (CI). CI algorithms have been coded in Matlab and are freely available from the link provided inside the book. The book demonstrates the ability of CI methodology for solving combinatorial problems such as Traveling Salesman Problem and Knapsack Problem in addition to real world applications from the healthcare, inventory, supply chain optimization and Cross-Border transportation. The inherent ability of handling constraints based on probability distribution is also revealed and proved using these problems.
Keywords: Computational intelligence.; Combinatorial optimization.; elektronické knihy; electronic books